IMPLEMENTASI MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN KERJA SAMA SISWA PADA PEMBELAJARAN IPA KELAS V SD - Albi Wijaya; Muhammad Suhdy (Teaching and General Education Studies, 2026)
This study aims to apply passing exercises using targets to improve the accuracy of passing on the inside of SSB Marga Sindang FC players in Lubuk Linggau City. The type of research used is pseudo-experimental research. The research was carried out at SSB Marga Sindang FC Lubuk Linggau City, with a sample of 20 futsal extracurricular participants. Data analysis includes normality test, t-test. Based on the average results of the pre-test and post-test, the score increased by 39.45. With the significance value of the tcal > table which is 10.981 > 1.729, Ho was rejected and Ha was accepted, thus it can be concluded that there is an increase in the implementation of passing exercises using targets on the accuracy of passing inside the foot of SSB Marga Sindang FC players in Lubuk Linggau City.